Forecasting labour supply and population: An integrated stochastic model - Johann Fuchs; Doris Söhnlein; Brigitte Weber; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
This paper presents a stochastic integrated model to forecast the German population and labour supply until 2060. Within a cohort-component approach, the population forecast applies principal components to birth, mortality, emigration and immigration rates. The labour force participation rates are estimated by means of an econometric time series approach. All time series are forecast by bootstrapping. This allows fully integrated simulations and the possibility to illustrate the uncertainties in the form of confidence intervals. Our new forecast confirms the results from former studies. We conclude that even rising birth rates and high levels of immigration cannot break the basic demographic trend in the long run. – – In der vorliegenden Studie wird die Bevölkerung und das Arbeitskräfteangebot für Gesamtdeutschland bis zum Jahr 2060 in einem integrierten Modell projiziert. Dazu werden im Rahmen eines Kohorten-Komponenten-Ansatzes Geburten, Sterbefälle, Zu- und Fortzüge mittels einer Hauptkomponentenanalyse (Principal Component Analysis) geschätzt. Die Erwerbsquoten werden mit einem ökonometrischen Zeitreihenmodell bestimmt. Mit einem stochastischen Ansatz (Bootstrapping) verwendet unsere neue Vorausberechnung eine Alternative zu der deterministischen Schätzmethode, die früheren IAB-Projektionen zugrunde lag. Das jetzige Modell ermöglicht vollständig integrierte Simulationen und erlaubt es, die existierenden Unsicherheiten in Form von Konfidenzbändern darzustellen. Die Ergebnisse bestätigen bekannte vorliegende Projektionen. Wir schließen daraus, dass auch steigende Geburtenraten und hohe Zuwanderung den grundlegenden demografischen Trend langfristig nicht brechen können.
Keywords: C38; J11; J20; J21; J22; 330; stochastic population forecast; principal components; demography; labour force participation; labour supply